Divergence, Gender, Violence, and Liberation: Four Questions from Six Different Readings of Seductive Spirits - Homewood, Nathanael J. (Journal of Africana religions, 2025)
Nathanael Homewood offers a response to six review articles of his book Seductive Spirits: Deliverance, Demons, and Sexual Worldmaking in Ghanaian Pentecostalism. In his response, Homewood pulls out four crucial questions from the reviews revolving around themes of divergence, gender, violence, and liberation, offering both agreement and disagreement with his readers.